The Analysis of conversational implicature of Elon Musk A.I and Mars in English Speech - Riska Gustiana; Agustinus Hary Setyawan (Tarbiatuna: Journal of Islamic Education Studies, 2024)
This study aims to discuss the importance of communication and conversational implicature in conveying meaning effectively. It highlights the significance of understanding the context and linguistic situation to prevent misinterpretation. The research aims to uncover and describe the types of conversational implicatures contained in Elon Musk's English public speech on A.I. and Mars, emphasizing the importance of analyzing implicatures in informal interactions. This study utilized a qualitative descriptive approach to analyze conversational implicatures in Elon Musk's discussions on A.I. and Mars in English speech. The research focused on identifying implicature types and functions in the conversations, with data collected from Elon Musk's public speeches and transcribed for analysis. The data reduction process involved constructing a data-collecting sheet, selecting relevant data, explaining and justifying the chosen facts, concluding, and verifying the accuracy of the information gathered.